KAJI NUMERIK DAN EKSPERIMENTAL LENDUTAN BALOK BAJA KARBON ST 60 DENGAN TUMPUAN ENGSEL - ROL - Mustafa Mustafa (Jurnal MEKANIKAL, 2012)
The aim of this study is to analyze the deflection phenomena of ST 60 steel with numerically and experimentally placed on the hinge-roller support. The study applies the integration method for numerical analysis and testing method for experimental ones. The supports use a hinge-roller with the material of carbon steel of ST 60 with length 0.8 m, width 0.01 m and thickness 0.01 m. The result shows that the maximum deflection occurs at x = 0.4 m with a loading of 2.5 kg for each location of loading. The value of deflection obtained experimentally was greater than of numerically.